Head injuries in sport. - Cantu, R C (1996)
Injuries to the head and neck are the most frequent catastrophic sports injury, and head injuries are the most common direct athletic cause of death. Although direct compressive forces may injure the brain, neural tissue is particularly susceptible to injury from shearing stresses, which are most likely to occur when rotational forces are applied to the head. The most common athletic head injury is concussion, which may very widely in severity. Intracranial haemorrhage is the leading cause of head injury death in sports, making rapid initial assessment and appropriate follow up mandatory after a head injury. Diffuse cerebral swelling is another serious condition that may be found in the child or adolescent athlete, and the second impact syndrome is a major concern in adult athletes. Many head injuries in athletes are the result of improper playing techniques and can be reduced by teaching proper skills and enforcing safety promoting rules. Improved conditioning (particularly of the neck), protective headgear, and careful medical supervision of athletes will also minimise this type of injury.